A Study on Digital Currency : the Safety of Future Money - T.Syahrul Reza (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2018)
Cryptography, as the most critical aspect of the never-ending evolving information technology era, is being criticized in its privacy aspect. Information outbreaks make users doubtful on relying on their own information in current cryptosystems. this study present professional countermeasures and attempts to define how the existing cryptology functioned being used worldwide by using Bitcoin as the prime. By understanding the current world phenomenon, it would be easier to answer the question of how secure and reliable cryptology actually is.